The Presence of Pathogenic Bacteria in School Children's Snack Food Samples in Medan City - Silaen, Srinatalia (Journal of Research in Science and Mathematics Education, 2024)
Purpose: Good and healthy food must be free from harmful and toxic substances, such as microbial contamination, chemicals, and other materials. The term School Children's Snack Food (PJAS) is a food that is found and routinely consumed by children in the school environment, food must meet the requirements of microbial contamination limits based on SNI (Indonesian National Standard) safety testing. The cause of food poisoning that is still a serious problem in various countries including Indonesia is pathogenic bacteria. The purpose of this study is to determine the presence of pathogenic bacteria in school children's snack food samples in Medan City in the Pematangsiantar area. Methodology: The methods used were the Nearest Approximate Count (JPT) of Escherichia coli, Bacillus sp. Number Test, Staphylococcus sp. Number Test, Salmonella Identification, and Total Plate Count (TPC). Findings: The test results on JPT Escherichia coli fried meatballs include SD M (9.9 ± 3.8) MPN/g, SD 5 (8.68 ± 2.73) MPN/g, SD IT (5.08 ± 0.66) MPN/g, and SD 4 (4.26 ± 2.44) MPN/g. The results of JPT Escherichia coli in fried meatballs in SD 1 and SD 2, as well as JPT E. coli ojek in all elementary schools, namely < 3 MPN/g. Significance: Conclusion that the snack food for elementary school children (fried and fried meatballs) in Pematangsiantar did not contain contamination with pathogenic bacteria Escherichia coli, Bacillus sp., Staphylococcus sp., Salmonella, and Total Plate Count (TPC).